Advances in the role of oxytocin receptors in human parturition. (5th July 2017) - Kim, Sung Hye; Bennett, Phillip R.; Terzidou, Vasso
Abstract: Oxytocin (OT) is a neurohypophysial hormone which has been found to play a central role in the regulation of human parturition. The most established role of oxytocin/oxytocin receptor (OT/OTR) system in human parturition is the initiation of uterine contractions, however, recent evidence have demonstrated that it may have a more complex role including initiation of inflammation, regulation of miRNA expression, as well as mediation of other non-classical oxytocin actions via receptor crosstalk with other G protein-coupled receptors (GPCRs). In this review we highlight both established and newly emerging roles of OT/OTR system in human parturition and discuss the expanding potential for OTRs as pharmacological targets in the management of preterm labour. Highlights: Role of OT/OTR system in parturition exceeds the initiation of uterine contractions. OT can trigger inflammation and regulation of miRNAs. Ligand-specific OTR/G-protein coupling can result in differential downstream signalling. Dimerisation of OTR and receptor crosstalk introduces novel strategies for the development of combination tocolytics. OTR could be used as a target for utero-specific tocolytic drug delivery.